Sinonasal malignancies: histopathological entities, regional involvement and long-term outcome - Lukas Anschuetz; Ralph Hohenberger; Christoph Kaecker; Olgun Elicin; Roland Giger; Marco Caversaccio (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background To assess a large patient cohort with sinonasal malignancies focusing on regional involvement, recurrence and oncological outcome. Methods Patients (n = 144) with malignant tumors of the nasal cavity and paranasal sinuses were treated at our tertiary referral center between 2008 and 2019. A chart review on patient and tumor characteristics, treatment and long-term outcome was performed. Results Most frequent histological types were squamous cell carcinoma (SCC) (n = 74), adenocarcinoma (n = 24) and mucosal melanoma (n = 18). Primary therapy was surgery in 66% of patients (n = 95) of which 65.8% (n = 66) received adjuvant radiotherapy. Twenty patients (13.8%) were initially staged as cN + and in seven cases, pN + status was histopathologically confirmed. Fifty-six of 130 patients (43.1%) had a relapse after curative intended therapy, including nine loco-regional (6.9%) and seven isolated regional recurrences (5.4%). Twelve of these 16 patients with (loco-)regional recurrence had SCC. Adenoid cystic carcinoma (87.5%) and SCC (65.3%) showed the best long-term overall survival. Conclusions Regional involvement and regional recurrence are scarce. Because of rarity and heterogeneity, evidence on therapeutic management is sparse resulting in the lack of clinical guidelines. Graphical Abstract